On the road to Mandalay: contribution to the Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) fauna of Myanmar with description of two new species - Poyarkov, Nikolay A (Zool Res, 2019)
We present a morphological and molecular assessment of the Microhyla fauna of Myanmar based on new collections from central (Magway Division) and northern (Kachin State) parts of the country. In total, six species of Microhyla are documented, including M. berdmorei, M. heymonsi, M. butleri, M. mukhlesuri and two new species described from the semi-arid savanna-like plains of the middle part of the Irrawaddy (Ayeyarwady) River Valley. We used a 2 481 bp long 12S rRNA–16S rRNA fragment of mtDNA to hypothesize genealogical relationships within Microhyla. We applied an integrative taxonomic approach combining molecular, morphological, and acoustic lines of evidence to evaluate the taxonomic status of Myanmar Microhyla. We demonstrated that the newly discovered populations of Microhyla sp. from the Magway Division represent two yet undescribed species. These two new sympatric species are assigned to the M. achatina species group, with both adapted to the seasonally dry environments of the Irrawaddy Valley. Microhyla fodiens sp. nov. is a stout-bodied species with a remarkably enlarged shovel-like outer metatarsal tubercle used for burrowing and is highly divergent from other known congeners (P-distance≥8.8%). Microhyla irrawaddy sp. nov. is a small-bodied slender frog reconstructed as a sister species to M. kodial from southern India (P-distance=5.3%); however, it clearly differs from the latter both in external morphology and advertisement call parameters. Microhyla mukhlesuri is reported from Myanmar for the first time. We further discuss the morphological diagnostics and biogeography of Microhyla species recorded in Myanmar.